Exercise simultaneously increases nasal patency and bronchial obstruction in asthmatic children. Issue 8 (6th July 2016) - Lukkarinen, Minna; Haavisto, Lotta E.; Lukkarinen, Heikki; Sipilä, Jukka I.; Papadopoulos, Nikolaos G.; Jartti, Tuomas
Abstract : We found that simultaneous post‐exercise increase in nasal patency and bronchial obstruction occurs only in children with atopic asthma, but not in sensitized children without asthma. In healthy children, the increase in nasal patency is accompanied by bronchial dilatation.